2019
DOI: 10.3390/f10050459
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Risks to Forest Biosecurity Associated with the Global Movement of Commercial Seed

Abstract: The import and export of tree seed carries with it risks of inadvertent introduction of pests and pathogens to hitherto unaffected regions. Although trade in seed of specified trees is regulated, phytosanitary requirements for most tree species are minimal, even those related to the most important forest tree species in a given region. A better understanding of the microbiome associated with seed intended for commercial production or ornamental use, and their potential risk with the transport from the source o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…In addition, Talgø et al () verified no symptom development in one of the three tests performed with the same strains, thus, suggesting that diverse abiotic and biotic factors can play an important role in the development of the disease, either by affecting the ecology of the pathogen or the susceptibility of the host. Moreover, Cleary et al () recently found S. polyspora in asymptomatic seeds of several Pinus spp. obtained across Europe and North America, including P. pinaster , P. radiata , P. strobus , P. sylvestris , P. mugo from Portugal and P. pinea from Turkey.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Talgø et al () verified no symptom development in one of the three tests performed with the same strains, thus, suggesting that diverse abiotic and biotic factors can play an important role in the development of the disease, either by affecting the ecology of the pathogen or the susceptibility of the host. Moreover, Cleary et al () recently found S. polyspora in asymptomatic seeds of several Pinus spp. obtained across Europe and North America, including P. pinaster , P. radiata , P. strobus , P. sylvestris , P. mugo from Portugal and P. pinea from Turkey.…”
Section: Resultsmentioning
confidence: 96%
“…Sydowia polyspora is also considered endophytic, being present in asymptomatic plants and in seeds (Cleary et al, ; Ridout & Newcombe, ). However, some authors suggested that the fungus may become pathogenic in a colonized host, under the influence of certain abiotic and biotic factors (Ridout & Newcombe, ; Talgø et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…, Cleary et al. , Liu and He ). Moreover, only pathogens that are transmitted to the seedling (vertical transmission) may represent a phytosanitary threat (Burgess and Wingfield ).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the countries (69%) the import of plant parts for human or animal consumption is subject to different regulations than propagation material (Table 1). However, the EU has not banned the import of fruit and seeds of any forest tree species, with potential consequences on forest health (Cleary et al 2019). It is worth remembering that if infected materials (fruits and seeds) are composted and used as a fertilizer the risk of pest establishment persists, since some organisms can survive the composting processing (Noble and Roberts 2004).…”
Section: Importmentioning
confidence: 99%
“…Hence, to avoid damage to plants in post-entry quarantine and lower the risk of introducing pests on the imported sentinel plants, it may be preferable to import plant propagation material other than rooted plants, such as seeds, parts of plants or tissue cultures (Anonymous 1999). The phytosanitary risk associated with imported plant propagation material is presumed to be lower than the risk associated with rooted plants (Cleary et al 2019;Franić et al 2019) and the regulations for import of such material are often more relaxed than those for other types of plants for planting (Eschen et al 2015a).…”
Section: Introductionmentioning
confidence: 99%